Kawasaki disease: an epidemiological study in central Italy. Issue 1 (December 2016) - Mauro, Angela; Fabi, Marianna; Da Frè, Monica; Guastaroba, Paolo; Corinaldesi, Elena; Calabri, Giovanni; Giani, Teresa; Simonini, Gabriele; Rusconi, Franca; Cimaz, Rolando
Abstract Background Kawasaki disease (KD) is a systemic vasculitis with an acute and self-limited course. The incidence of KD differs widely among ethnic groups and is higher in the Asian population. In Italy, no recent data are available. Our purpose is to define the epidemiology of Kawasaki disease in the years 2008–2013 in children aged < 14 years in the Italian regions of Tuscany and Emilia Romagna through administrative data. Methods We studied the epidemiology of KD in the years 2008–2013 in children 0–14 years old resident in Tuscany and in Emilia Romagna regions using hospital ICD-9 discharge codes with a thorough data cleaning for duplicates. Results The distribution of the KD patients across ages was similar for the two regions with a peak in the second year of life. When considering data of the two regions together, the rate of incidence was 17.6 for 100, 000 children under 5 years. For both Regions the incidence rose slightly during the study period and had a seasonal distribution, with higher incidence in spring and winter. Conclusion This is the first Italian study performed through the use of administrative data. Figures are in line but slightly higher than those published in other European countries.